Cocktail of Hyaluronic Acid and Human Amniotic Mesenchymal Cells Effectively Repairs Cartilage Injuries in Sodium Iodoacetate-Induced Osteoarthritis Rats - Wang, Ai-Tong; Zhang, Qing-Fang; Wang, Nuo-Xin; Yu, Chang-Yin; Liu, Ru-Ming; Luo, Yi; Zhao, Yu-Jie; Xiao, Jian-Hui (Frontiers in Bioengineering and Biotechnology, 2020)
Osteoarthritis (OA) is one of the most common but refractory degenerative articular cartilage diseases. The emerging human amniotic mesenchymal cells (hAMSCs) have been identified a promising stem cell source in cartilage repair, and hyaluronic acid (HA) is a versatile regulator for stem cell transplantation. Herein, an effective and straightforward intra-articular injection therapy using the cocktail of hAMSCs and HA is developed to treat knee OA in a rat model. The injured cartilage is remarkably regenerated to a very close level to normal cartilage after 56 days of treatment. Both hAMSCs and HA are indispensable organic components in this therapy, in which HA can synergistically enhance the effects of hAMSCs on cartilage repair. The regenerative mechanism is attributed to the fact that the addition of HA comprehensively enhances the activities of hAMSCs, including chondrogenic differention, proliferation, colonization, and regenerative modulation. The therapy paves a new venue on injection therapy of OA, holding the potential to realize rapid clinical translation.